Genotypic and phenotypic characterization of Escherichia coli isolated from indigenous individuals in Malaysia - Vanitha, Mariappan; Soo, Tein Ngoi; Yvonne Ai, Lian Lim; Romano, Ngui; Kek, Heng Chua; Cindy Shuan, Ju Teh (Mashhad University of Medical Sciences, 2022)
Objective(s): The occurrence of asymptomatic verocytotoxin (VT)-producing Escherichia coli (VTEC) infections among humans in recent years is posing a high risk to public health. Thus, the role of asymptomatic human carriers as a source of dissemination should not be underestimated. This study aimed to elucidate the phenotypic and genotypic characteristics of E. coli in the stool samples collected from indigenous individuals in Malaysia. Materials and Methods: E. coli strains (n=108) were isolated from stool samples obtained from 41 indigenous individuals. All strains were subjected to Repetitive Extragenic Palindromic-Polymerase Chain Reaction (REP-PCR) typing and confirmation of VTEC variants. Non-duplicate strains were selected based on REP-PCR profiles and further subjected to antimicrobial susceptibility test (AST). The genotypic and phenotypic characteristics of the strains were then correlated with the demographic data of the subjects. Results: A total of 66 REP-PCR profiles grouped in 53 clusters (F=85%) were obtained. Four genetically distinct strains were confirmed as VTEC (eaeA-positive). The predominant resistance was against ampicillin (34.2%), followed by trimethoprim-sulfamethoxazole (32.9%), ampicillin-sulbactam (5.5%), and ciprofloxacin (1.4%). All isolates were sensitive to amoxicillin-clavulanate, cefuroxime, ceftriaxone, imipenem, and meropenem. Conclusion: Genetically diverse E. coli and VTEC strains were found to colonize the intestines of the indigenous populations. This study is important for the prospective surveillance of E. coli among the indigenous individuals in Malaysia, especially in asymptomatic VTEC infection and antimicrobial resistance phenomenon.